The impact of climate change on agriculture sector in Malaysia / Najihah Mohamad Sharif - Mohamad Sharif, Najihah (2021)
The effects of climate change on agriculture have gotten a lot of attention in Malaysia as it is a significant contributor to public Gross Domestic Product (GDP). The depth of the effect of climate change is certainly hard to examine because of inconclusive findings and weakness in identifying the impact to the agriculture sector. This research is aimed at investigating the impact of climate change towards the agriculture productions on the economy. Conceptual framework is created to recognize the impacts of climate change on the agriculture sector in Malaysia. The variables that have been used in this study are the agricultural sector, carbon dioxide, electric power consumption, energy consumption and temperature. The study reveals that temperature has a major effect on the agricultural sector. Therefore, good measurement of its impacts on agricultural production is needed to ensure long run agricultural sustainability in Malaysia